Modal cutoff properties of a fiber with a trefoil cross section under the weak guidance approximation - Sharma A.; Khastgir P.; Singh O.N. (My University, 2025)
In this paper, we present a theoretical analysis of the propagation of electromagnetic waves through a fiber with a trefoil cross section. This may be regarded as a preliminary study of a waveguide in which three cores are embedded in a common cladding. By choosing an appropriate coordinate system, the scalar ware equation is soiled, and thereby the characteristic equation for the guided modes under the weak guidance approximation is derived. To understand the basic modal properties in a simple manner, the cutoff equation is derived, and the modal cutoff properties of some modes are determined numerically. © 1997 John Wiley & Sons, Inc.